Plants vs. Streams: Their groundwater‐mediated competition at “El Morro”, a developing catchment in the dry plains of Argentina - Jobbagy Gampel, Esteban Gabriel; Lorenzo, Santiago; Buono, Nicolás; Páez, Ricardo; Diaz, Yésica; Marchesini, Victoria; Nosetto, Marcelo Daniel (Wiley, 2021)
Our understanding of how groundwater mediates evapotranspiration/streamflow partitioning is still fragmented and catchment studies under changing vegetation conditions can provide a useful frame for integration. We explored this partition in a flat sedimentary dry catchment in central Argentina in which the replacement of native vegetation with rainfed crops was accompanied by the abrupt formation of groundwater‐fed streams by subsurface erosion (i.e. sapping) episodes. Historical records indicated widespread water table rises (~0.3 m y‐1 on average). Groundwater level and stream baseflow fluctuated seasonally with minima in the warm rainy season, indicating that evaporative discharge rather than rainfall shapes saturated flows. Diurnal groundwater level fluctuations showed that plant uptake was widespread where water tables are shallow (<3 m) but restricted to deep‐rooted Prosopis forests where they are deep (7‐10 m). MODIS and LANDSAT NDVI revealed a long‐term greening for native vegetation, new wetlands included, but not for croplands, suggesting more limited evapotranspiration‐groundwater level regulation under agriculture. Close to the deepest (20 m) and most active incisions, groundwater level and greenness declined and stream baseflow showed no seasonal fluctuations, hinting decoupling from evapotranspiration. Intense ecological and geomorphological transformations in this catchment exposed the interplay of five mechanisms governing evapotranspiration/streamflow partition including (i) unsaturated uptake and both (ii) riparian and (iii) distributed uptake from the saturated zone by plants, as well as (iv) deepening incisions and (v) sediment deposits over riparian zones by streams. Acknowledging the complex interplay of these mechanism with groundwater is crucial to predict and manage future hydrological changes in the dry plains of South America.